2005
DOI: 10.1139/w04-122
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of charcoal rot pathogen,Macrophomina phaseolina, into specific groups using URP-PCR

Abstract: Forty isolates of Macrophomina phaseolina, a pathogen causing charcoal dry root rot of soybean, cotton, and chickpea, were genetically characterized with universal rice primers (URP; primers derived from DNA repeat sequences in the rice genome) using polymerase chain reaction (URP-PCR). Out of 12 URPs used in this study, 5 primers were effective in producing polymorphic fingerprint patterns from the DNA of M. phaseolina isolates. Three primers (URP-2F, URP-6R, and URP-30F) were quite informative and produced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 15 publications
5
40
0
Order By: Relevance
“…A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010). The high genetic diversity of this pleomorphic fungal species is reflected not only in isolates from distinct hosts and geographical origins but also within isolates collected from a single host or geographical origin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010). The high genetic diversity of this pleomorphic fungal species is reflected not only in isolates from distinct hosts and geographical origins but also within isolates collected from a single host or geographical origin.…”
Section: Resultsmentioning
confidence: 99%
“…Different molecular methods have been used for differentiating M. phaseolina populations including Restriction Fragment Length Polymorphism (RFLP) of rDNA-ITS regions (Aghakhani and Dubey, 2009;Almeida et al, 2003;Purkayastha et al, 2006;Su et al, 2001), Random Amplified Polymorphic DNA (RAPD) (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Almeida et al, 2003;Almeida et al, 2008;Babu et al, 2010;Das et al, 2006;Jana et al, 2003;Omar et al, 2007;Purkayastha et al, Rajkumar and Kuruvinashetti, 2007;Su et al, 2001;Zade et al, 2009), Amplified Fragment Length Polymorphism (AFLP) (Brooker et al, 2008;Mayek-Perez et al, 2001;Reyes-Franco et al, 2006;Saleh et al, 2010;Vandemark et al, 2000), Universal Rice Primer PCR (URP-PCR) (Jana et al, 2005b), Inter simple sequence repeats (ISSR) (Jana et al, 2005a;Purkayastha et al, 2008), Repetitive SequenceBased Polymerase Chain Reaction (Rep-PCR) (Purkayastha et al, 2008) and SSR (Baird et al, 2010). Inter simple sequence repeat (ISSR) markers are powerful tools which can be utilized to access the variation in the flanking regions of microsatellite loci that are dispersed throughout all genomes (Zietkiewicz et al, 1994).…”
mentioning
confidence: 99%
“…Based on the degree of polymorphism indicated by the percent of polymorphic loci generated and Shannon's index, URP2R was more suitable for studying genetic diversity in populations of both subgroups. In general, both URP and ISSR marker systems have been useful for evaluating variation in fungal populations (Aggarwal et al 2010;Jana et al 2005;Kiyosi et al 2005;Sharma et al 2005;Stodart et al 2007). The UPGMA dendrogram showed two main clusters separating subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on population genetics of R. solani or other plant pathogens using dominant markers such as RAPD, URP, AFLP or ISSR have reported that geographic location or host specificity or both had an effect on population structure (Aggarwal et al 2010;Duncan et al 1993;Jana et al 2005;Stodart et al 2007). Because of the limitations of dominant markers, these studies are difficult to compare with other studies where co-dominant markers (microsatellites) were used.…”
Section: Discussionmentioning
confidence: 99%
“…URP-PCR protocol employed stringent PCR with high annealing temperature throughout the thermo-cycling reaction, affording high reproducibility. URP-PCR technique is a useful tool for the characterization and grouping of most eukaryotic or prokaryotic genomes, especially at inter-and intraspecies levels (Kang et al, 2000;Jana et al, 2005).…”
Section: Introductionmentioning
confidence: 99%